2002
DOI: 10.1186/cc1703
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: To describe the epidemiology of the acute respiratory distress syndrome (ARDS) in a Brazilian ICU. Methods: This prospective observational, non-interventional study, included all consecutive patients with ARDS criteria [1] admitted in the ICU of a Brazilian tertiary hospital, between January 1997 and September 2001. Were collected in a prospective fashion the following variables: age, gender, APACHE II score at ICU admission and at ARDS diagnosis, cause of ARDS, presence of AIDS, cancer and immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…ICUs, found mortality rates of 11, 33.9, 46.9 and 52.2% respectively in patients with systemic inflammatory response syndrome (SIRS), sepsis, severe sepsis and septic shock (15) . Another Brazilian study analyzed data from 75 ICUs in different regions and found mortality rates of 16.7% for sepsis, 34% for severe sepsis and 65.3% for septic shock (16) .…”
Section: Discussionmentioning
confidence: 99%
“…ICUs, found mortality rates of 11, 33.9, 46.9 and 52.2% respectively in patients with systemic inflammatory response syndrome (SIRS), sepsis, severe sepsis and septic shock (15) . Another Brazilian study analyzed data from 75 ICUs in different regions and found mortality rates of 16.7% for sepsis, 34% for severe sepsis and 65.3% for septic shock (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, não comparamos a população séptica com portadores de outras doenças. O declínio de qualidade de vida pósalta hospitalar de pacientes sépticos observado no nosso e em outros estudos é similar ao que se observa em pacientes com lesão pulmonar aguda (LPA) ou síndrome do desconforto respiratório agudo (SDRA), doença pulmonar obstrutiva crônica (DPOC) e insuficiência cardíaca congestiva (ICC) (10,(25)(26)(27), assim como em outras doenças agudas graves (7,(28)(29)(30)(31)(32). Considerando que a sepse é uma das principais complicações dos pacientes graves e a principal causa de LPA/SDRA, não é possível determinar se os efeitos observados a longo prazo são decorrência exclusiva da sepse, da LPA/SDRA ou da doença aguda subjacente (10).…”
Section: Discussionunclassified
“…The BASES study showed an incidence of sepsis of 57 per 1,000 inhabitants, with a higher incidence of neoplasias in groups with infection compared to groups with systemic inflammatory response without infection, 18.3 and 12.1%, respectively. 15 In 65 ICUs in Brazil, high mortality due to sepsis was detected at 28 days in 2006; 46.6% with description of neoplasia in 14% of the patients, with 8% under immunosuppressive treatment. 16 The demand for hospitalization in the ICU for patients with neoplasia varied in different studies between 15% 14 and 21.5% 5 ; 85% had solid neoplasia and 25% hematological neoplasia; 25% of the solid tumors were metastatic.…”
Section: Introductionmentioning
confidence: 99%